PERTOBATAN EKOLOGIS GUNA MENJAGA ALAM CIPTAAN - Maria, Maria mulalinda; Rattu, Andreas (Department of Theology - Sekolah Tinggi Filsafat Seminari Pineleng, 2025)
This article discusses the theme of ecological repentance to maintain the integrity of creation. The background to this article is the fact that environmental damage threatens the life of nature, both humans and other creatures. Environmental damage encourages humans to change the way they think, feel, and act in relation to creation. This is what is meant by ecological repentance. This repentance must begin with the will of the heart and culminate in concrete actions and behaviors that maintain the integrity of the environment. Without ecological repentance, we will continue to witness environmental destruction, which also has negative effects on human life. Ecological repentance is an urgent call for humanity to re-realize the profound connection between humans and the universe as God's creation. In a world increasingly beset by environmental crises such as climate change, forest destruction, water and air pollution, and biodiversity extinction, ecological repentance becomes a form of moral and spiritual reflection on human lifestyles that have often been consumptive, exploitative, and unsustainable.